PENGARUH LATIHAN TEMBAKAN INSTEP DRIVE TERHADAP KETERAMPILAN SHOOTING PADA TEAM SSB DURI GALAXY - Crieshandi, Fegi; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the effect of instep drive shooting practice on shooting skills on SSB Duri Galaxy team. The researcher took SSB Duri Galaxy team, amounting to 16 people, as the population of the study. The researcher used the total sampling technique of saturated sample where all population sampled. The design of this study used pretest-posttest approach. The instrument taken is by shooting the target on the wall to measure the skills. After that, the data were processed by statistics, to test the normality by lilifors test at a significant level of Î± (0.05). The hypothesis proposed is the effect of instep drive shooting exercises on shooting skills. Based on statistical data analysis, it yields pretest data Lcount 0,1221, data posttest Lcount 0,1766 and Ltable 0,213, mean Lcount <Ltabel. Then the data is normally distributed. Based on t test analysis yielded Tcount equal to 6,30 and Ttabel 1,753, mean Tcount> T table. Thus, we can concluded that there are Effect of Instep drive fire training on shooting skills on the SSB Duri Galaxy team.Keywords: Drive Instep Shot, Shooting Skill